2005
DOI: 10.1111/j.1365-2133.2005.06647.x
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometric analysis of cellular infiltrate from American tegumentary leishmaniasis lesions

Abstract: Variable amounts of gammadelta lymphocytes were present in all lesions, with no association with duration of illness. The highest percentages of interleukin-2R- and interferon-gammaR-positive cells were observed in ML lesions and could render these T cells more susceptible to the effects of these cytokines. The distribution of intralesional T-lymphocyte subsets was quite variable (CD4+ > CD8+ = 18 cases, CD8+ > CD4+ = 12 cases and CD4+ congruent with CD8+ = 4 cases) without any association with clinical parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
62
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(70 citation statements)
references
References 38 publications
6
62
0
2
Order By: Relevance
“…Several reports have suggested that a huge influx of T cells takes place in lesions [4,7,8], as not only is a higher frequency observed of local lymphocytes responding to L. braziliensis in comparison with blood [9], but also an increased proportion of T CD4 + and T CD8 + cells is reported in older lesions [5,6]. Although the effector T cell response mounted in response to the parasite can lead to a cure, it also seems to be responsible for tissue damage [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several reports have suggested that a huge influx of T cells takes place in lesions [4,7,8], as not only is a higher frequency observed of local lymphocytes responding to L. braziliensis in comparison with blood [9], but also an increased proportion of T CD4 + and T CD8 + cells is reported in older lesions [5,6]. Although the effector T cell response mounted in response to the parasite can lead to a cure, it also seems to be responsible for tissue damage [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…An incisional biopsy from the skin lesion border was performed for diagnostic purposes, and part of the tissue fragment was separated for cell extraction. Mononuclear cells from leishmaniasis lesions (LeMC) were obtained as described elsewhere [6]. In brief, the skin specimen, stripped of subcutaneous fat, was placed into a tissue sieve, fitted with a 64 mm mesh filter and containing RPMI supplement.…”
Section: Acquisition Of Mononuclear Cells From Blood and Leishmaniasimentioning
confidence: 99%
See 2 more Smart Citations
“…Infections by Leishmania lead to a specific activation of the host immune response (9). Studies indicate the importance of the balance between T CD4 + and CD8 + cells, in which the first ones would have their proportion reduced during the healing process (10,11).…”
Section: Short Communicationmentioning
confidence: 99%